The endoparasitic protozoan and nematode in commercialized and non-commercialized Gallus gallus / Shakina Vedora Yafle - Yafle, Shakina Vedora (2017)
A study was conducted in February to June, 2017 on the endoparasitic prevalence of phylum protozoa and nematode in commercial (broiler and layer) and noncommercial poultry farms located in Kota Kinabalu and Sandakan, Sabah. The aims of the study were to determine the types of endoparasites prevalent in each of the farms, to measure the rate of prevalence and also to compare the prevalence rates statistically. There were 180 replicated samples of chicken dung taken from three different places 'were preserved with 10% formalin solution, brought to the laboratory of UiTM, Sabah for egg examination and counted by using direct smear, floatation technique and McMaster egg per count technique. The results has shown that ten species of both protozoan and nematodes were present namely Heterakis sp., Ascaridia sp., Capillaria sp., Tricostrongylus sp., Enterobius sp., Eimeria sp., Cryptosporidium sp., Cystoisopora sp., Sarcocystis sp. and Entamoeba sp. The highest prevalence rate measured was 100% and the lowest was 5%, while nematode worms illustrated higher in number as compared to protozoan in overall. In commercial broiler, commercial layer and non-commercial farms, the prevalence rate of endoparasitic infection were 72.75%, 82.3% and 80.7% respectively. The data was further compared by using IBM SPSS Ver.23 and non-parametric test (Kruskal-Wallis test) was conducted to assess the difference between the independent variables with significant value of 0.05. The outcomes ( X 2 = 39.38, p < 0.05) shown was that there were significant differences between the prevalence rate of commercial (broiler and layer) and non-commercial farms. More significant infestations of endoparasitic was reported in non-commercial poultry followed by in commercial broiler and lastly in the commercial layer farm. This study recommended that the poultry farms to emphasize and level up the biosecurity system for better disease and infection control in the future.